1999
DOI: 10.4037/ajcc1999.8.4.220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relaxing music on cardiac autonomic balance and anxiety after acute myocardial infarction

Abstract: BACKGROUND: Acute myocardial infarction places additional demands on an already compromised myocardium. Relaxing music can induce a relaxation response, thereby reversing the deleterious effects of the stress response. OBJECTIVES: To compare the effects of relaxing music; quiet, uninterrupted rest; and "treatment as usual" on anxiety levels and physiological indicators of cardiac autonomic function. METHODS: A 3-group repeated measures experimental design was used. Forty-five patients, 15 per group, with acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
2
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(101 citation statements)
references
References 0 publications
7
82
2
10
Order By: Relevance
“…There are some other interventions aimed at reducing anxiety (McCaffrey & Taylor 2005). These interventions include behaviour therapy, cognitive behaviour therapy, music therapy, sensory information, progressive muscle relaxation, guided imagery, biofeedback, humour and story telling (Buttler et al 1991, Cason et al 1992, Barnason et al 1995, White 1999. Research on the effectiveness of these interventions before cardiac catheterization is limited.…”
Section: Discussionmentioning
confidence: 99%
“…There are some other interventions aimed at reducing anxiety (McCaffrey & Taylor 2005). These interventions include behaviour therapy, cognitive behaviour therapy, music therapy, sensory information, progressive muscle relaxation, guided imagery, biofeedback, humour and story telling (Buttler et al 1991, Cason et al 1992, Barnason et al 1995, White 1999. Research on the effectiveness of these interventions before cardiac catheterization is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Increased HRV provides evidence of greater PSNS activity and the physiologic response of relaxation. Classic works have documented the impact of several alternative therapies on HRV, such as relaxation training (Sakakibara, Takeuchi, & Hayano, 1994), music therapy (White, 1999), and biofeedback (Cowan, Kogan, Burr, Hendershot, & Buchanan, 1990;Hatch, Borcherding, & Norris, 1990). More recently, Lombardi (2002) acknowledged that HRV is incompletely understood, but he supported the use of HRV as a noninvasive method of evaluating ANS changes that may have clinical utility and therapeutic implications.…”
Section: Heart Rate Variability As a Measure Of Relaxationmentioning
confidence: 99%
“…Power spectral analysis can be explored over speci¢c time periods allowing for detailed interpretation about HRV before, during, and following an intervention. In particular, power of the LF and HF HRV bands can be examined as physiologic measures of relaxation (White, 1999;White & Porth, 2000), as shown in Figure 1.…”
Section: Heart Rate Variability As a Measure Of Relaxationmentioning
confidence: 99%
“…12 Studies investigating heart rate variability after relaxation showed a parasympathetic predominance in healthy adults 13 and in post cardiac arrest patients. 14 Savasana is an important part of Hatha Yoga relaxation practice. To our knowledge, there is no study addressing the influences of savasana on sympathovagal balance of hypertensive subjects.…”
Section: B Introductionmentioning
confidence: 99%